Attention Distraction and Its Relationship with Electronic Games Among Preparatory School Female Students in the Eastern Branch Schools in Zliten City - Soosiy, Noura Al Hady; Haidar, Reem Ateya; Hamouda, Najah Ibrahim; Al Ghuwail, Awatef Ateya (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The study aimed to explore the level of distraction suffered by middle school students (seventh grade), in addition to revealing the relationship between distraction and electronic games among these students in some schools of the eastern branch in the city of Zliten, the descriptive approach was used, and data was collected through a questionnaire, where the study sample consisted of (51) female students from the targeted schools, who were selected in a simple random manner. The results of the study showed a strong relationship between distraction and playing electronic games, as it was found that these games have a negative impact on students’ concentration and academic level, the study also recommended the need to prepare programs to enhance attention and concentration, in addition to raising awareness of the dangers of electronic games.